Diseño y simulación de una máquina clasificadora de patatas para la semillera Miranda de la ciudad de San Pedro de Pelileo. - Chicaiza Guato, Sergio Alejandro (2021)
The objective of this project is to design and simulate a potato sorting machine with the proposed topic, it was proposed to evaluate with computational software and with a possibility of evaluating the system through the finite element method (FEM) this is a topic that becomes relevant in recent years at the company level, the parallel roller sorting machine was designed, since it offers multiple benefits the machine can be disassembled into modules to be transported. The sorting system is designed with two conveyor belts, which have the configuration of rollers, the project uses quantitative methodology which considers variables and compares them, this is of vital importance for the design of the rollers, criteria from the Manufacturing book were used. Engineering and Technology of KalpakJian S and Schmid S using the CAE software, an analysis of deformation, stresses, moments that occur in the structure and components of the additional classification system was obtained, a static study was carried out using the software to determine which material is the Taking into account the Ecuadorian market, two steels were taken into account for multiple advantages: AISI 304 steel and ASTM A36 steel. The static study was carried out to determine the results such as deformation, safety factor and for the simulation of the classification process. used the CAD / CAE software where the multi-counting system was represented, the work is presented as a solution to the problem of product classification.